PEMBUATAN GAME PARTY MULTIPLAYER 2D “ARCATE MANIA” PADA PLATFORM PC - Virginia Virginia; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
“Arcate Mania” is a two-dimenional arcade party game which contains 10 minigames that can be played by two to four players. The game was created using Unity 2D game engine for PC platform. Rewired are used as plugins to configure multiplayer feature and control for minigames. Photoshop were used to design characters and other 2D images for the game. Each minigames have different gameplay and theme. Players have to compete to collect points by winning minigames. Testing was done by blackbox testing method, alpha testing method by lecturers, and beta testing method by survey form given to 44 respondents. The results show that “Arcate Mania” is a multiplayer game with interesting graphic that is easy to play for people with range from teenage to adult and support different kinds of controllers.